Contribution of Dr. B.R. Ambedkar towards Indian Society: Examining the Impact of Dr. B.R. Ambedkar on Indian Society (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Dr. Ambedkar was an extraordinary patriot, social mastermind, political reformer, philosophical essayist with dynamic thoughts. He represented all political, social and social activities which expanded the explanation of human advancement and satisfaction. He was the spirit for the constitution of India. He campaigned for the advancement of the abused and discouraged classes. He stood uncommon crusading soul, cutting out in this method assumes significant job for himself between the main engineers of current India. In this procedure, Dr. Ambedkar rises not just as a Valliant upholder of the Indian equitable republic, yet too catches the extraordinarily unmistakable spot in the Indian Pantheon as an unordinary scholarly mass pioneer who stirred the social still, small voice of contemporary India.